Association of parental workaholism and body mass index of offspring: A prospective study among Japanese dual workers - Takeo eFujiwara; Akihito eShimazu; Masahito eTokita; Kyoko eShimada; Masaya eTakahashi; Izumi eWatai; Noboru eIwata; Norito eKawakami (Frontiers in Public Health, 2016)
The purpose of the study was to investigate the association between parental workaholism and child body mass index (BMI) among Japanese dual-income families. In 2011, 379 dual-income families from urban Tokyo with children aged 0–5 years were recruited for a baseline survey, and 160 (42.2%) were followed up in 2012. Demographics, workaholism, work demands, work control, time spent with children, and parental and child weights and heights were assessed using a questionnaire. Structural equation modeling was performed to determine the association between maternal and paternal workaholism in 2011 and child BMI in 2012, considering the mediating effects of time spent with children. Paternal workaholism showed a direct significant positive association with child BMI after 1 year (standardized coefficient: 0.19; p < 0.001), while maternal workaholism was not associated with child BMI. Both maternal and paternal time spent with children did not mediate the association. Paternal work demands showed a strong positive association with workaholism, but paternal work control did not. Paternal, but not maternal, workaholism was associated with an increase in child BMI over 1 year. Interventions that target workaholism by reducing paternal work demands might be effective in preventing overweight in offspring.